THE IMPACT OF NON-MONETARY INCENTIVE ON EMPLOYEES COMMITMENT IN TELECOMMUNICATION SECTOR IN LIBYA - Abdussalam Ayad A Kerdasi; S.M. Ferdous Azam (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
The key objective of the study is to inspect the relationship between non-monetary incentives (career advancement opportunities and development opportunities) and employee commitment among the workers working in the telecommunication companies of Libya. The moderating role of perceived supervisory support has been evaluated on the relationship between non-monetary incentives and employee commitment. For the sake of statistical analysis, the SPSS and PLS-SEM software were used to analyze data. Data analysis showed that the theoretical model developed for the sake of the present study effectively explained the significant effect of non-monetary incentives on employee commitment. However, the statistical finding revealed that supervisory support has a moderating role only on the relevance between career advancement opportunities and employee commitment. For development opportunities, the perceived supervisory support was found with no moderating effect.